Giant pelvic well-differentiated liposarcoma - Luben Stokov; Asen Todorov; Panayot Kurtev; Elka Angelova; Georgi Georgiev; Luben Lubenov Stokov (Journal of the Bulgarian Orthopaedics and Trauma Association)
Herein, we report a case of a giant well-differentiated liposarcoma located subgluteally and extending into the pelvis through the obturator foramen, nearby the urinary bladder and rectum without causing functional disturbances. The tumor was removed simultaneously with transgluteal posterior and anterior transabdominal approach. Six months postoperatively, no clinical and radiological evidence of recurrence was observed.